An investigation into factors that determine the growth rate in the Islamic banking and finance - Huma Nawaz (Future Business Journal, 2019)
The purpose of this study is to determine the impact of products and services of Islamic finance in Pakistan. This study has involved an empirical analysis of the environmental factors of growth and its impact on the growth of Islamic Financial Institutions. To investigate the factors of growth, a structural equation model develops that incorporates the main determinants of growth of banking assets and equity funds. The growth in the Islamic equity funds and banking assets has been identified as definite antecedents of growth in the Islamic financial system. The empirical investigation by the structural model using Pakistani dataset revealed that four out of ten hypotheses were significant including two direct paths as antecedents of annual growth. This study provides empirical support for the influence of some development factors to control the barriers of growth in the Islamic finance industry. This paper allows the identification of the major development factors of Islamic financial system that takes into account the importance of operational strategy and environment for the growth of Islamic equity funds and banking assets.
Keywords: G10; G14; G15; G17; G21; 650; Structural equation model; Ethical finance; Islamic financial system; Islamic products and services; Growth; Islamic banking; Islamic equity fund; Pakistani finance